Changes in leg-spring behavior during a 5000m self-paced run in differently trained athletes - Girard, O.; Millet, G.; Slawinski, J.; Racinais, S.; Micallef, J. P. (Science & Sports, 2010)
Aims.To explore whether fatigue-induced changes in spring-mass behavior during a 5000m self-paced run varied according to the runner`s training status. Methods and results. Six highly- and six well-trained triathletes completed a 5000m time trial. Running velocity and vertical stiffness decreased significantly (P < 0.05) with fatigue, whereas leg stiffness remained constant. None of these parameters displayed a significant interaction between fatigue and training status, despite vertical stiffness being higher (P < 0.05) in highly-trained triathletes. Conclusions.During a 5000m self-paced run, impairments in leg-spring behavior that occur with fatigue are not affected by athletes` training status.